Contribution of alkaline phosphatase to phosphorus cycling in natural riparian zones in the Wangyu River running into Lake Taihu. Issue 44 (19th September 2016) - Ren, Lingxiao; Wang, Peifang; Wang, Chao; Peng, Zhicheng; Hu, Bin; Wang, Ruizhe
Abstract: Understanding phosphorus (P) cycling is essential to reducing algal blooms and other negative effects in water. However, few studies have investigated the contributions of alkaline phosphatase (APase) or alkaline phosphatase activity (APA) to P cycling in natural riparian zones. Here, seasonal and spatial development of plankton, P fractions, APA fractions, and fluorescence labeled enzyme activity were investigated in a natural riparian zone in the main diversion channel for water transfer into Lake Taihu. Plankton greatly benefited from APase, and APA production was their important advantage for P acquisition and proliferation. Fluorescence labeling varied greatly between species and seasons, indicating different adaptive strategies for dissolved organic P acquisition. Phytoplankton experienced severe P stress when they were the main APA producers in spring and summer, but bacteria were superior P competitors. During autumn and winter, free APA dominated, phytoplankton APA (phyt-APA) deceased because of low biomass or high dissolved reactive P (DRP) and bacterial APA (bact-APA) proportions were high. Bulk APA and DRP were negatively correlated for the entire data-set and during the productive seasons. Significant negative correlation was observed between phyt-APA and DRP in the lacustrine and wetland zones, but the situation was complicated for bact-APA, probably owing to organic carbon limitation.